THE INFLUENCE OF RELIGION ON THE ROMAN LEGAL SYSTEM - Andreea RÎPEANU (Challenges of the Knowledge Society)
The origins of the science of Roman law are closely related to traditional religious practices. In the old era, it was reduced to knowing forms, kept secret by pontiffs, like religious rites. It is in fact the consequence of the confusion existent between ius, honestum and fas. Therefore, both the juridical consultations, and the religious ones were strictly provided individually and confidentially, considering the secret contents thereof, with a view to maintain the influence of a closed caste over population. All this period, when it was perpetuated a tradition taken over from prestate period, lasted until the year 301 before Christ, under the name of sacred or religious jurisprudence.